Teknik 3D Conformal Radioterapi (3DCRT) Pada Keganasan Sinus Paranasal Dengan Modalitas Linac - Fitri Agustina; Jeffri Ardiyanto; Siti Masrochah (Jurnal Imejing Diagnostik (JImeD), 2020)
Background: Radiotherapy is a radiation therapy action using ionizing radiation. To obtain the maximum dose of radiation in the tumour and the lowest possible dose on critical organs required a technique of radiation technique 3 Dimensional Conformal Radiotherapy (3DCRT). Radiotherapy Unit Radiology Installation Dr Sardjito Hospital Yogyakarta using 3DCRT technique. This research aims to know the radiotherapy procedure on paranasal sinus cancer using 3DCRT technique, to know the implementation of bolus beam modifier and dose optimization with the addition of electron radiation.Methods: The type of research in this thesis is qualitative research with case study approach. The research was conducted at Radiotherapy Unit Radiology Installation Dr Sardjito Hospital Yogyakarta after published Ethical Clearance.  Methods of data collection in this study are observation, interviews, and documentation.Result: The results of this study indicate that the radiotherapy procedure in paranasal sinus cancer using 3DCRT technique can produce a homogeneous dose distribution, the implementation of bolus beam modifier is capable of generating dosage homogeneity on uneven target surfaces, and the distribution of doses with electron radiation on the target in the surface area can be optimal.Conclusion: With these techniques, the goal of radiotherapy can be achieved is to give the maximum dose in the tumour and the minimum dose possible in healthy tissue located in the vicinity.